Association of COVID-19 mortality with politics and on-demand testing in 217 U.S. counties - Leon S. Robertson (BMC, 2021)
Abstract Background Previous research found increased COVID-19 spread associated with politics and on-demand testing but not in the same study. The objective of this study is to estimate the contribution of each corrected for the other and a variety of known risk factors. Methods Using data from 217 U.S. counties of more than 50,000 population where testing data were available in April, 2021, the associations of COVID-19 deaths with politics, testing and other risk factors were examined by Poisson and least squares regression. Results Statistical controls for 15 risk factors failed to eliminate the association of COVID mortality risk with percent of vote for Donald Trump in 2016 or negative tests per population. Each is independently predictive of increased mortality. Conclusion Apparently, many people who test negative for the SARS-CoV-2 virus engage in activities that increase their risk, a problem likely to increase with the availability of home tests. There is no association of negative tests with the Trump vote but, according to polling data, Trump voters' past resistance to public health recommendations has been extended to resistance to being vaccinated, threatening the goal of herd immunity.